ASTROLOGI ISLAM KEPULAUAN DI KESULTANAN TIDORE - Syarifudin Syarifudin (DIALEKTIKA, 2019)
ABSTRACT This research is concerned with Islamic Islamic astrology. This research problem focuses on the identification of Islamic archipelagic astrology in Tidore Kesulatanan as a contribution in society, especially for marginal people who do not have the knowledge and the cost of treatment in the hospital. This research is characterized by phenomenology in Tidore Islands Islamic Astrology. This study uses a multiparadigm approach in looking at social reality. The results of this study found there are 9 types of black magic that is used as a media disrupt social social life, and there are 14 white science that has a major contribution to maintain the mental health and physical health of Islamic islands in the city of Tidore. The contribution of Islamic astrology has become a tradition that is orally transformed. The term astrology is also known as mat science. Islamic archipelagic astrology contributes to maintaining social balance. Modern astrology uses the great cost of Islamic astrology of the islands less costly in the healing process for humanity. Key Word: Astrology, Islam, and the Archipelago.